Prinsip-Prinsip Administrasi Pendidikan - Nur, Sapridah; Hasanah Usnur, Uswatun (STAI Tebing Tinggi Deli, 2024)
Administration as a joint activity exists everywhere as long as it exists humans who live and work together in groups. If we see a the factory works to produce some kind of object as its product, so there we see there is administration. If we look at an institution that trains and give a lesson that they finally get a certificate from education process, then there is administration. If we look a group of people together worship something as a symbol of power who is considered almighty or takes care of other spiritual needs in a way regularly, then there is also administration. Educational administration has a very important role in the educational process. Because the educational administration section is very broad, educational administration can be used as a determinant of goals and formulating policies in general so that it can be a tool for measuring educational progress. Educational administration greatly influences the quality of education. If the administration of an educational institution has a good structure and runs well, the quality of education will increase. Vice versa, if the educational administration structure is not good and has problems, then the quality of education can decline and an evaluation must be carried out immediately. The principles of educational administration are a basis or guideline that is used as a guideline for achieving educational goals. Because by having a basis or the right principles then educational administration will be successful.